AB0607 Clinical profile of filipino patients with systemic lupus erythematosus. (12th June 2018) - Santiago, A.-T.M.; Tee, M.; Tee, C.
Abstract : Objectives: To determine the clinical profile of Filipino SLE patients as determined using the 2012 Systemic Lupus Collaborating Clinics (SLICC) criteria. Methods: We checked which among the SLICC criteria were fulfilled by Filipino SLE patient when we examined them and their case records, as part of a nationwide genetic study on SLE conducted from October 2015 to March 2017. Results: Two hundred twenty-five patients who were diagnosed to have SLE after 18 years of age were evaluated. The mean age of the population at the time of evaluation was 37.76 years. Females comprised 98% of our population. Mean age of onset was 30.68-year-old, while the mean age at diagnosis was 31.52-year-old. Acute cutaneous rash was found in 82%; arthritis 80%; non-scarring alopecia 65%; oral ulcers 52%; renal disorder 41%; chronic cutaneous rash in 28%; leukopenia 23%; hemolytic anaemia 17%; thrombocytopenia 16%; serositis 13%; and neurologic disorder 6%. Anti-nuclear antibody was present in 88%; low complement 33%; antidsDNA in 29%; direct Coombs' 4%; antiphospholipid antibody 2%; and anti-Smith antibody in 2%. Kidney biopsy was performed in only 6% (15/225) of patients, 33% of whom had Class IV histopathologic results. Conclusions: Filipino SLE patients typically present with acute cutaneous rash, arthritis, nonscarring alopecia and oral sores. Renal disorder, hematologic and neurologic manifestations are found to be less common among them. Finally, it was noted that renal biopsy is not commonly performed among these patients. Disclosure of Interest: None declared